Biomaterials and Tissue Engineering for Regenerative Repair of Articular Cartilage Defects - Kâzım Tur, (Archives of Rheumatology, 2009)
Articular cartilage defects heal very poorly and lead to degenerative arthritis. Existing medications cannot promote healing process; cartilage defects eventually require surgical replacements with autografts. As there is not enough source of articular cartilage that can be donated for autografting, materials that promote cartilage regeneration are important in both research and clinical applications. Tissue engineering involves cell growth on biomaterial scaffolds in vitro. These cells are then injected into cartilage defects for biological in vivo regeneration of the cartilage tissue. This review aims first to provide a brief introduction to the types of materials in medicine (biomaterials), to their roles in treatment of diseases, and to design factors and general requirements of biomaterials. Then, it attempts to sum up the recent advances in engineering articular cartilage; one of the most challenging area of study in biomaterials based tissue engineering, as an example to the research on regenerative solutions to musculoskeletal problems with an emphasis on the biomaterials that have been developed as scaffolds for cartilage tissue engineering. The definitive goal on cartilage regeneration is to develop a system using biomimetic approach to produce cartilage tissue that mimics native tissue properties, provides rapid restoration of tissue function, and is clinically translatable. This is obviously an ambitious goal; however, significant progress have been made in recent years; and further advances in materials design and technology will pave the way for creating significantly custom- made cellular environment for cartilage regeneration. (Turk J Rheumatol 2009; 24: 206-17)